Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil - José Floriano Barêa Pastore; Guilherme Medeiros Antar (European Journal of Taxonomy, 2021)
The Cerrado domain is the most diverse savannah biome in the world and a biodiversity hotspot for conservation. Only a few areas of the domain remain well preserved, among them the Jalapão region in Tocantins State, currently is considered the best preserved area of the Brazilian Cerrado. Listed in a recent Angiosperm checklist for the region, there were two species of Polygala series Trichospermae, which were recognized as new by the first author. Polygala bringelii sp. nov., endemic to the Jalapão region, is diagnosed by its obclavate seeds without a ring of trichomes at their base, keel with the crest shorter than the cuculus, and the internal sepals (wings) longer than the capsule. Polygala tocantinensis sp. nov., endemic to Tocantins state, is distinguished by its internal sepals (wings) with two glands near to the rounded apex, and a ring of convergent trichomes at the base of the seeds. The two species are morphologically closest with Polygala trichosperma of sect. Timutua, series Trichospermae, but differs in its corolla and seeds shape and pubescence. An identification key, photographic plates, photos of floral parts under magnification, preliminary conservation assessments, and ecological comments of both species are also provided.